USING PODCAST AS AUTHENTIC MATERIALS TO DEVELOP STUDENTS’ SPEAKING SKILL - Roviqur Riziqien Alfa (Universitas Sarjanawiyata Tamansiswa, 2020)
This paper aims at giving insight and ideas about the use of podcasts as authentic material to promote student’s speaking skills. Podcast is a digital media that contains recorded programs from television, radio, and interviews. Since this media provides audio from English native speakers, it can help language learners to improve their speaking skills as a model. Many researchers believe that podcasts can be alternative media to improve the student’s speaking skills. According to Chan et al. (2011), since the podcast is one of the alternatives, the teacher can fairly easy to provide authentic material in teaching. In this case, the teacher will be a facilitator to improve the student’s speaking skills by implementing podcasts inside or outside classroom activity as the media.